2016
DOI: 10.1007/s11325-016-1398-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep-disordered breathing in acute coronary syndrome: a systemic review and meta-analysis

Abstract: High prevalence of all SDB, moderate-to-severe SDB, and severe SDB was found in ACS patients. It is clinically important to screen for SDB in patients with ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
1
7
1
Order By: Relevance
“…Furthermore, since all studies included in the meta-analysis established the diagnosis after hospital admission, this proportion may estimate the true prevalence of undiagnosed OSA. As a comparison, a recent systematic review and meta-analysis of 32 studies of ACS patients reported a pooled prevalence of sleep-disordered breathing (SDB) at 69%, 43%, and 25% using diagnostic thresholds of AHI > 5, 15, 30 events per hour, respectively [49]. In contrast to our analysis, these studies did not distinguish between OSA and CSA, and therefore contribute to a higher estimate of SDB.…”
Section: Prevalence Of Osa Among Hospitalized Cvd Patientscontrasting
confidence: 86%
“…Furthermore, since all studies included in the meta-analysis established the diagnosis after hospital admission, this proportion may estimate the true prevalence of undiagnosed OSA. As a comparison, a recent systematic review and meta-analysis of 32 studies of ACS patients reported a pooled prevalence of sleep-disordered breathing (SDB) at 69%, 43%, and 25% using diagnostic thresholds of AHI > 5, 15, 30 events per hour, respectively [49]. In contrast to our analysis, these studies did not distinguish between OSA and CSA, and therefore contribute to a higher estimate of SDB.…”
Section: Prevalence Of Osa Among Hospitalized Cvd Patientscontrasting
confidence: 86%
“…Another area of current interest is whether OSA may modify the outcomes of acute coronary syndromes (ACS). OSA prevalence is high in patients with ACS, and severe OSA occurs in 25% of the patients [39]. The ongoing ISAACC trial (Impact of Continuous Positive Airway Pressure on Patients with ACS and Nonsleepy OSA) will provide long-term data on the effects of treating OSA in this population [40].…”
Section: Common Comorbidities In Osa Patientsmentioning
confidence: 99%
“…Studies using portable devices with limited numbers of parameters (cardiorespiratory polygraphy) showed a pooled prevalence of 77%, while polysomnography studies demonstrated a mean prevalence of 60%. The authors did not find substantial differences between studies performed in different ethnic groups [29]. These data on OSA in ACS patients clearly exceed the figures of SDB in the general population.…”
Section: Osa and Acs: Associations Sex Differences And Phenotypingmentioning
confidence: 64%
“…The consequences of breathing disturbances during sleep (sleep disordered breathing (SDB)), including hypoxia/re-oxygenation, oxidative stress, systemic inflammation, arousals and increased work of breathing, suggest a correlation between OSA and ACS. HUANG et al [29] performed a meta-analysis to evaluate the prevalence of SDB in ACS. They analysed 32 studies including 3360 patients.…”
Section: Osa and Acs: Associations Sex Differences And Phenotypingmentioning
confidence: 99%